2023
DOI: 10.1038/s41598-022-26750-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure to immersive computer-generated virtual nature and control environments on affect and cognition

Abstract: Previous research has shown that exposure to immersive virtual nature environments is able to induce positive affective and physiological effects. However, research on the effects on cognitive performance is scarce. Additionally, the effects of virtual nature exposure compared to a virtual control environment with a comparable amount of virtual objects have not been examined so far. Therefore, we conducted an experiment with 27 participants to study the psychological effects of such exposure. The virtual natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 90 publications
2
17
1
Order By: Relevance
“…Our results align with previous studies:Kalantari et al (2022) concluded that there was an improvement in mood changes after experiencing VR.Similarly,Mostajeran et al (2023) have stated that the involvement of virtual nature positively impacts mood and stress levels. However, they did not investigate the relationship between embodiment and altering VR contents or the degree of control.…”
supporting
confidence: 92%
“…Our results align with previous studies:Kalantari et al (2022) concluded that there was an improvement in mood changes after experiencing VR.Similarly,Mostajeran et al (2023) have stated that the involvement of virtual nature positively impacts mood and stress levels. However, they did not investigate the relationship between embodiment and altering VR contents or the degree of control.…”
supporting
confidence: 92%
“…VR is also becoming more and more popular in mobile applications. It can provide an alternative to actual outdoor immersion through 3D images that realistically simulate real scenes, giving people a feeling of immersion (e.g., positive effects on cognition [36] and stress relief [37]). The application of virtual technology to promote relaxation and to benefit attentional resources, cognitive performance, and pain experience is being supported by more research [38].…”
Section: Mobile Technology Application and Virtual Reality Nature Int...mentioning
confidence: 99%
“…Research shows that natural alternatives (photos and videos) can approximate real nature, making the body relaxed and restored [40]. The forest environments presented via a head-mounted display had a positive effect on the participants' cognition [36]. Studies have demonstrated that virtual exposure to a forest environment is effective in reducing stress and anxiety caused by confinement in a limited space [37,41].…”
Section: Mobile Technology Application and Virtual Reality Nature Int...mentioning
confidence: 99%
See 1 more Smart Citation
“…Even in virtual environments, similar positive effects of simulations of nature using immersive virtual reality (VR) technology have been observed 24 , 25 . For instance, as a result of exposure to immersive virtual nature previous studies have reported improvements in mood 26 , 27 and cognitive performance 28 , 29 , recovery from stress 30 , as well as reductions of anxiety 31 , 32 and negative emotions such as fatigue and depression 33 .…”
Section: Introductionmentioning
confidence: 99%